Therapeutic potential of mesenchymal stem cell-derived exosomes and miRNAs in neuronal regeneration and rejuvenation in neurological disorders: a mini review - Salehpour, Aria; Karimi, Zahra; Ghasemi Zadeh, Mokhtar; Afshar, Mohammadreza; Kameli, Ali; Mooseli, Fatemeh; Zare, Masoud; Afshar, Alireza (Frontiers in Cellular Neuroscience, 2024)
Mesenchymal stem cells (MSCs) have gained considerable attention in the field of regenerative medicine due to their ability to secrete small extracellular vesicles (EVs) known as exosomes. This review delves into the various biological activities of MSCs and the cell interactions enabled by these exosomes, with a focus on their potential for neuronal regeneration and the treatment of neurological disorders. We scrutinize findings from multiple studies that underscore the neuroprotective and neuro-regenerative effects of exosomes derived from MSCs, illuminating their mechanisms of action and therapeutic applications. This review thoroughly investigates all related pathways, miRNAs, and factors to suggest potential strategies for enhancing therapy for neurological disorders using exosomes and miRNAs, and for boosting neuronal regeneration.